Move to strike - O'Shaughnessy, Perri (Delacorte Press, 2001)
With a business to run, a son to raise and a complicated personal life, renegade lawyer Nina Reilly is used to having as much drama in her own home as the courthouse. Now she has a make-or-break case on her hands